Measuring Stakeholder Relations in Green Last-Mile Deliveries in the E-commerce Market in Cities - Mucowska, Magdalena (Pomiar relacji interesariuszy zielonych dostaw ostatniej milina rynku e-commerce w miastach, 2024)
Aim: This research aimed to investigate the intricate relations among stakeholders involved in urban green last-mile deliveries (GLMD) within the e-commerce market, with a focus on network relation features such as strength, reciprocity, and proximity. Methodology: A literature review identified measurable components of network relation features, followed by an expert study. The study assessed the weights of identified components within the network relation features – strength, reciprocity, and proximity. Results: The findings revealed that strength is the most critical network relation feature, followed by proximity and reciprocity. Within the strength component, commitment and trust were identified as crucial. Trust is the most critical factor within reciprocity components, whereas within proximity organizational and social dimensions gain prominence. Implications and recommendations: The research provided practical insights for shaping relations among urban green last-mile delivery stakeholders. Local governments and courier company managers can leverage the findings to consciously shape stakeholder relations, facilitating environmental and quality-of-life objectives. Originality/value: The research addressed a gap in the literature by focusing on the network dynamics of stakeholders in green last-mile delivery, acknowledging their critical role in environmental sustainability.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 5, s. 69-80
Keywords: last-mile delivery; stakeholders; network; e-commerce; city; dostawy ostatniej mili; interesariusze; sieć; miasta